2011
DOI: 10.1002/jctb.2630
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Cu(II) onto agricultural materials from tropical regions

Abstract: BACKGROUND: In Ghana, the discharge of untreated gold mine wastewater contaminates the aquatic systems with heavy metals such as copper (Cu), threatening ecosystem and human health. The undesirable effects of these pollutants can be avoided by treatment of the mining wastewater prior to discharge. In this work, the sorption properties of agricultural materials, namely coconut shell, coconut husk, sawdust and Moringa oleifera seeds for Cu(II) were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 31 publications
(47 reference statements)
2
25
0
5
Order By: Relevance
“…The decrease in the initial metal concentration prolonged the breakthrough curve and required higher treatment time for the saturation. Similar nature of the breakthrough curve has been reported by Acheampong et al for Cu(II) removal using coconut shells as bioadsorbent.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The decrease in the initial metal concentration prolonged the breakthrough curve and required higher treatment time for the saturation. Similar nature of the breakthrough curve has been reported by Acheampong et al for Cu(II) removal using coconut shells as bioadsorbent.…”
Section: Resultssupporting
confidence: 86%
“…The dried biomass was powdered and sieved. Density, surface area, and porosity for the dried MSB were measured using standard methods available for analysis of biosorbents . The pH zpc (point of zero charge) was determined using standard method available in the literature .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study on gold sorption using a series of different Amberlite XAD resins impregnated with an ionic liquid (Cyphos IL101, a tetraalkyl phosphonium chloride) has shown that the sorption performance is correlated with IL loading in terms of sorption capacity and that uptake kinetics are strongly influenced by both the IL loading and the textural properties of the resin . SEM‐EDX (scanning electron microscopy coupled with energy dispersive analysis of X‐ray) was already used for the characterization of sorbent materials (composition, homogeneity, distribution of functional groups or ion‐exchangers), the dispersion of target metals in the sorbent, but also for the interpretation of diffusion profiles and mass transfer mechanisms . Chaigneau et al used SEM‐EDX to follow the transport parameters in porous media affected by in situ mineral precipitation .…”
Section: Introductionmentioning
confidence: 99%
“…Lignocellulosic wastes have been widely studied for metal removal from water and are considered to be comparable to sorbents from other natural sources, with advantages resulting from their availability, low-cost and simple operational process (Miretzky and Cirelli 2010). Among them, it is possible to refer the use of agriculture wastes such as rice milling by-products (Tarley and Arruda 2004), rice bran (Fatima et al 2013), carrot residues (Nasernejad et al 2005), orange waste (Marín et al 2009(Marín et al , 2010, coconut husk (Acheampong et al 2011), grape bagasse (Farinella et al 2007), and sorghum straw, oats straw and agave bagasse (Bernardo et al 2009). …”
Section: Introductionmentioning
confidence: 99%